Clathrin-adaptor ratio and membrane tension regulate the flat-to-curved transition of the clathrin coat during endocytosis - Delia Bucher; Felix Frey; Kem A. Sochacki; Susann Kummer; Jan-Philip Bergeest; William J. Godinez; Hans-Georg Kräusslich; Karl Rohr; Justin W. Taraska; Ulrich S. Schwarz; Steeve Boulant (Nature Communications, 2018)
The sequence of structural and molecular events during clathrin-mediated endocytosis is unclear. Here the authors combine correlative microscopy and simple mathematical growth laws to demonstrate that the flat patch starts to curve when around 70% of the final clathrin content is reached.